FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISPASI MASYARAKAT DI BANK SAMPAH CANGKIR HIJAU KECAMATAN METRO TIMUR KOTA METRO - Fatin Haniyah; Sri Maryati; Husna Tiara Putri (Lembaga Penelitian, Pengabdian Masyarakat, dan Penjaminan Mutu (LP3) ITERA, 2022)
Like other urban areas, Metro City has a waste problem. An alternative solution that has been carried out by the government in dealing with waste problems is through the waste bank program. One of the waste bank that has many achievements in Metro City is Cangkir Hijau Waste Bank, but the lack of community participation in participating in this waste bank results in the least amount of garbage that can be processed by Cangkir Hijau Waste Bank. Therefore, the purpose of this study is to determine the factors that influence community participation in Cangkir Hijau Waste Bank. To answer these objectives, it is carried out: 1) Identification of the conditions of community participation in Cangkir Hijau Waste Bank; 2) Analysis of the factors that influence community participation in Cangkir Hijau Waste Bank. In this research, the method used is descriptive analysis and crosstab association analysis with probability sampling technique. The sampling method used was proportional clustered random sampling with a sample of 155 respondents. After researching that the condition of community participation participating in Cangkir Hijau Garbage Bank only amounted to 1% or 2 people from 155 respondents. Meanwhile, the factors that influence community participation in Cangkir Hijau Garbage Bank are attitudes, knowledge, environmental benefits, and profits.